Calculation of the influence of the entropy of stars on the Earth's exosphere and the theory of entropic gravity - Violeta N Nikolić (Annals of Mathematics and Physics - Peertechz Publications, 2023)
In the first part of this study, the entropic contribution of star objects, observable during the night between November 13 and 14, 2021, in the sky above Belgrade (Lat. 44o 49' 04'' N, Long. 20o 27' 25'' E, mean Elev. 117 m), Serbia, to the thermodynamic equilibrium of the Earth's exosphere, was determined. In the second part of the study, the force of gravitational attraction between the considered star objects and the Earth was calculated, by applying entropic gravity theory. The obtained results shed new light on the importance of star objects for sustaining the Earth's thermodynamic system.